Misyari Rasyid Alafasyi’s “Qolbi Muhammad” Song Lyrics: Michael Riffaterre’s Semiotic Study - Dihyat Haniful Fawad; Muassomah Muassomah; Helmi Syaifuddin (Journal of Arabic Literature (JaLi), 2022)
The purpose of this study is not only to reveal the heuristic meaning in the lyrics of the song "Qolbi Muhammad" by Misyari Rasyid Alafasyi, but also to reveal the hermeneutic meaning in the song "Qolbi Muhammad" by Misyari Rasyid Alafasyi. This research is a qualitative descriptive research. The primary data sources in this study were the lyrics of the song "Qolbi Muhammad" by Misyari Rasyid Alafasyi, and the secondary data sources in this study were scientific papers, books, and other references. Data collection techniques using text analysis techniques and literature study. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The findings of this study are based on the heuristic meaning of the song "Qolbi Muhammad" by Misyari Rasyid Alafasyi, the researchers found the results of lexical meaning in the form of advice from a Munsyid, namely Misyari Rasyid Alafasyi to mankind in general and to Muslims in particular to always be on His path that has been exemplified by the Prophet Muhammad. so that we are always in the protection of Allah swt. As for the results of the hermeneutic meaning in the song, the researchers found a matrix or essence of the song, namely the indicator of the existence of a servant is his faith and devotion to Allah swt and how he relates to the Prophet Muhammad. This means that a servant must always increase his faith and devotion to Allah swt by following the path or teachings brought by the noblest role model, namely the Prophet Muhammad.